ESTUDO COMPARATIVO ENTRE DUAS UNIDADES DE PRODUÇÃO AGROPECUÁRIA VITIVINICULTORAS DO MUNICÍPIO DE IJUÍ / RS - Oliveski, Felipe E.; Garcia, Dagmar C.; Uhde, Leonir T.; Fernandes, Sandra B. V.; Carbonera, Roberto (Salão do Conhecimento, 2013)
Resumo